2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26994
|View full text |Cite
|
Sign up to set email alerts
|

Future Time Perspective and Self-Regulated Learning: Multiple Case Studies in Industrial Engineering

Abstract: Lisa Benson is an Associate Professor of Engineering and Science Education at Clemson University, with a joint appointment in Bioengineering. Her research focuses on the interactions between student motivation and their learning experiences. Her projects involve the study of student perceptions, beliefs and attitudes towards becoming engineers and scientists, and their problem solving processes. Other projects in the Benson group include effects of student-centered active learning, self-regulated learning, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…This study also found that these students fit in one of these three FTP cone types 12 . And a fourth study focused on replicating the results of the previous studies with a new population-freshmen engineering students (n=7) at a western land-grant institution 13 .…”
Section: Previous Worksupporting
confidence: 62%
See 2 more Smart Citations
“…This study also found that these students fit in one of these three FTP cone types 12 . And a fourth study focused on replicating the results of the previous studies with a new population-freshmen engineering students (n=7) at a western land-grant institution 13 .…”
Section: Previous Worksupporting
confidence: 62%
“…She also wants to get an anthropology minor and study abroad to make her more qualified for a job that allows her to travel. The fact that she narrowed down her future goals and is able to describe these goals beyond her first job after graduation fits with other Sugar Cone students; however, there was not as much definition as other Sugar Cone students we have interviewed in previous studies [5][6][7]12 . She also sees these ideal future goals as realistic, as we would expect for a Sugar Cone student.…”
Section: Nikki's Interviewmentioning
confidence: 96%
See 1 more Smart Citation
“…We will expand the quantitative and qualitative studies to further test and magnify our findings, and explore how engineering students' FTPs affect their self-regulated learning strategies and processes, particularly sub-goaling 4 . We will focus on completing a large portion of the longitudinal study by doing follow up surveys and interviews with students who took the MAE survey as first year students 2 and 3 years ago.…”
Section: Future Workmentioning
confidence: 91%
“…Additionally, more detailed descriptions of the qualitative research that addresses RQ2 are provided elsewhere [3][4] .…”
Section: Introductionmentioning
confidence: 99%